2022
DOI: 10.1038/s41467-022-29146-2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide maps of nucleolus interactions reveal distinct layers of repressive chromatin domains

Abstract: Eukaryotic chromosomes are folded into hierarchical domains, forming functional compartments. Nuclear periphery and nucleolus are two nuclear landmarks contributing to repressive chromosome architecture. However, while the role of nuclear lamina (NL) in genome organization has been well documented, the function of the nucleolus remains under-investigated due to the lack of methods for the identification of nucleolar associated domains (NADs). Here we have established DamID- and HiC-based methodologies to gener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(94 citation statements)
references
References 73 publications
8
85
1
Order By: Relevance
“…When comparing dcHiC to existing approaches, we showed that it identifies regions with higher differences in replication timing, Lamin B1 signals, and differentially expressed genes, suggesting better prioritization of relevant biological regions. Even though differences of compartmentalization between ESC and NPC generally aligned with changes in Lamin B1 association, a recent work highlighted the importance of nucleolus association in revealing layers of compartmentalization with distinct repressive chromatin states [63]. Our initial analysis showed that over 10% of all significant compartment differences we found between ESC and NPC belongs to nucleolus associated domains (NADs) that were deemed exclusive to either ESC or NPC [63] providing an explanation for a subset of differences in compartmentalization during differentiation .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…When comparing dcHiC to existing approaches, we showed that it identifies regions with higher differences in replication timing, Lamin B1 signals, and differentially expressed genes, suggesting better prioritization of relevant biological regions. Even though differences of compartmentalization between ESC and NPC generally aligned with changes in Lamin B1 association, a recent work highlighted the importance of nucleolus association in revealing layers of compartmentalization with distinct repressive chromatin states [63]. Our initial analysis showed that over 10% of all significant compartment differences we found between ESC and NPC belongs to nucleolus associated domains (NADs) that were deemed exclusive to either ESC or NPC [63] providing an explanation for a subset of differences in compartmentalization during differentiation .…”
Section: Discussionmentioning
confidence: 73%
“…Even though differences of compartmentalization between ESC and NPC generally aligned with changes in Lamin B1 association, a recent work highlighted the importance of nucleolus association in revealing layers of compartmentalization with distinct repressive chromatin states [63]. Our initial analysis showed that over 10% of all significant compartment differences we found between ESC and NPC belongs to nucleolus associated domains (NADs) that were deemed exclusive to either ESC or NPC [63] providing an explanation for a subset of differences in compartmentalization during differentiation . Expanding to a three-way (n=3) mouse neuronal differentiation model, we showed that dcHiC continues to systematically identify critical biological marker genes and can recover cell-specific functions from differential compartment analysis alone.…”
Section: Discussionmentioning
confidence: 73%
“…When comparing dcHiC to existing approaches, we showed that it identifies regions with higher differences in replication timing, Lamin B1 signals, and differentially expressed genes, suggesting better prioritization of relevant biological regions. Even though differences in compartmentalization between ESCs and NPCs are generally aligned with changes in the lamin B1 association, a recent work highlighted the importance of nucleolus association in revealing layers of compartmentalization with distinct repressive chromatin states [63]. Our initial analysis showed that over 10% of all significant compartment differences we found between ESC and NPC belong to nucleolus-associated domains (NADs) that were deemed exclusive to either ESC or NPC [63], providing an explanation for a subset of differences in compartmentalization during differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Even though differences in compartmentalization between ESCs and NPCs are generally aligned with changes in the lamin B1 association, a recent work highlighted the importance of nucleolus association in revealing layers of compartmentalization with distinct repressive chromatin states [63]. Our initial analysis showed that over 10% of all significant compartment differences we found between ESC and NPC belong to nucleolus-associated domains (NADs) that were deemed exclusive to either ESC or NPC [63], providing an explanation for a subset of differences in compartmentalization during differentiation. Expanding on a three-way (n=3) mouse neuronal differentiation model, we showed that dcHiC continues to systematically identify critical biological marker genes and can recover cell-specific functions from differential compartment analysis alone.…”
Section: Discussionmentioning
confidence: 99%
“…A logical follow up question is what factors might contribute to the extent of structural variation. There are various essential factors such as epigenetic marks, associated structural proteins, and nuclear lamina associations that vary in a cell-type specific manner and contribute to the organization of 3D genome (40)(41)(42). Therefore, investigating the role of these different factors in the variation of chromosome structural ensemble is of high importance.…”
Section: Introductionmentioning
confidence: 99%